The Role of Proopiomelanocortin and α-Melanocyte-Stimulating Hormone in the Metabolic Syndrome in Psychiatric Disorders: A Narrative Mini-Review - Raue, Stefan; Wedekind, Dirk; Wiltfang, Jens; Schmidt, Ulrike (Frontiers in Psychiatry, 2019)
The metabolic syndrome (MetS) comprises abdominal obesity, preclinical or full diabetes type 2, arterial hypertension and dyslipidemia and affects a significant proportion of the general population with a remarkably higher prevalence in patients suffering from psychiatric disorders. However, studies exploring the pathogenetic link between MetS and psychiatric diseases are rare. Here, we aim to narrow this gap in knowledge by providing a narrative review on this topic that focusses on two psychiatric diseases, namely on schizophrenia and posttraumatic stress disorder (PTSD) since we assume them to be associated with two different main causalities of MetS: in schizophrenia, MetS evidently develops or aggravates in response to antipsychotic drug treatment while it assumingly develops in response to stress-induced endocrine and/or epigenetic alterations in PTSD. First, we compared the prevalences of MetS and associated pathologies (which we took from the latest meta-analyses) among different psychiatric disorders and were surprised that the prevalences of arterial hypertension and hyperglycemia in PTSD almost doubles those of the other psychiatric disorders. Next, we performed a literature search on the neurobiology of MetS and found numerous articles describing a role for proopiomelanocortin (POMC) in MetS. Thus, we concentrated further analysis on POMC and one of its downstream effector hormones, α-melanocyte-stimulating hormone (α-MSH). We found some evidence for a role of POMC in both PTSD and schizophrenia, in particular in antipsychotic-induced MetS, as well as for α-MSH in schizophrenia, but, surprisingly, no study on α-MSH in PTSD. Taken together, our synopsis reveals, first, a potential interaction between the POMC system and stress in the assumingly at least partially shared pathogenesis of psychiatric disorders and MetS, second, that modulation of the POMC system, in particular of the melanocortin 3 and 4 receptors, might be a promising target for the treatment of MetS and, third, that the DNA methylation status of POMC might speculatively be a promising biomarker for MetS in general and, possibly, in particular in the context of stress-related psychiatric conditions such as PTSD. To best of our knowledge, this is the first review on the role of the POMC system in MetS in psychiatric disorders.